The French Hannibal. Antiquity, Intertextuality and Evaluation of Napoleon Bonaparte in the Italian Campaign in the British and Polish Press (1796-99) - Matylda Włodarczyk (Lea)
This case study pursues connections between editorial stance and allusions to antiquity, focusing on the use of the “French Hannibal” designation, used to characterise Bonaparte in the early stage of the French Revolutionary Wars. The paper addresses the so far poorly explored interfaces of evaluation and intertextuality in historical news discourse. In terms of a diachronic and comparative perspective, the analysis shows that whereas editorial stance was easy to discern in the British news of the time, Polish news sources had not yet developed a series of shared conventions to express editorial opinion.